Theoretical Aspects of The Use of Adapted Authentic Texts in Teaching a Foreign Language (Eurasian Research Bulletin, 2022)
Authentic materials are among the most important tools a teacher can and must use in class in order to make his/her teaching go smoothly and be effective in transmitting the necessary knowledge to all students. The article discusses the effect of using authentic materials in teaching, because a number of studies point out that the use of authentic materials is regarded a useful means to motivate learners, arouse their interest and expose them to the real language they will face in the real world